The additional values of microarray allergen assay in the management of polysensitized patients with respiratory allergy - Passalacqua, G.; Melioli, G.; Bonifazi, F.; Bonini, S.; Maggi, E.; Senna, G.; Triggiani, M.; Nettis, E.; Rossi, R. E.; Vacca, A.; Canonica, G. W. (Allergy (Copenhagen), 2013)
Background The IgE response is directed against specific components from an allergenic source. The traditional diagnostic methods use whole extracts, containing allergenic, nonallergenic and cross‐reactive molecules. This may pose diagnostic challenges in polysensitized patients. Microarray techniques detect specific IgE against multiple molecules, but their value in term of additional information and economic saving has not been yet defined. Objective We assessed the additional diagnostic information provided by an allergen microarray in a large population of polysensitized subjects. Methods In this multicentre study, allergists were required to carefully record diagnosis and treatment of consecutive patients referred for asthma/rhinitis, using the standard methodology (history, skin prick test, IgE assay). Then, a microarray allergen assay was carried out. Clinicians were required to review their diagnosis/treatment according to microarray results. Results 318 allergic patients (30% reporting also nonrespiratory symptoms) and 91 controls were enrolled. The clinicians reported at least one additional information from the microarray in about 60% of patients, this resulting in therapeutic adjustments. In 66% of patients IgE to pan‐allergens were detectable, being this clinically relevant in 38% of patients with polysensitization to pollens. Conclusion Microarray IgE assay represents an advancement in allergy diagnosis, as a third‐level approach in polysensitized subjects, when the traditional diagnosis may be problematic.